The role of non-audit fees in audit quality: a field study on audit firms operating in the Gaza Strip (Palestine Technical College Journal for Research and Studies, 2023)
The study aimed to identify the role of non-audit fees in audit quality. The study adopted the descriptive approach through designing a questionnaire for data collection. The study sample consisted of (40) employees working in audit firms, of which (33) valid questionnaires were retrieved for statistical analysis. Statistical analyses were conducted using the Statistical Package for the Social Sciences (SPSS) to obtain the study results. The findings revealed that there were no statistically significant differences at the significance level (α ≤ 0.05) regarding the role of non-audit fees in audit quality attributable to the variables of educational qualification, specialization, age, and years of experience. The study recommended that company managements should develop consulting, financial, and accounting services in order to identify future financial needs, in addition to training external auditors and enhancing their professional competence in a way that improves audit quality.
Keywords: non-audit fees; audit quality; external auditing; audit firms